2017
DOI: 10.7554/elife.23966
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of localization and function of the transcriptional co-activator YAP by angiomotin

Abstract: The Hippo-YAP pathway is a central regulator of cell contact inhibition, proliferation and death. There are conflicting reports regarding the role of Angiomotin (Amot) in regulating this pathway. While some studies suggest a YAP-inhibitory function other studies indicate Amot is required for YAP activity. Here, we describe an Amot-dependent complex comprised of Amot, YAP and Merlin. The phosphorylation of Amot at Serine 176 shifts localization of this complex to the plasma membrane, where it associates with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 60 publications
6
75
0
Order By: Relevance
“…Arid1A-SWI/SNF do not affect YAP/TAZ nuclear localization; thus, this pathway acts in conjunction with angiomotins, the Hippo pathway, and other factors that influence YAP/TAZ nuclear localization. Angiomotins have also been reported in the nucleus (80), and it will be interesting in future studies to determine whether they can regulate YAP/TAZ in the nucleus in response to changes in nuclear F-actin.…”
Section: Nuclear Actin Sensingmentioning
confidence: 99%
“…Arid1A-SWI/SNF do not affect YAP/TAZ nuclear localization; thus, this pathway acts in conjunction with angiomotins, the Hippo pathway, and other factors that influence YAP/TAZ nuclear localization. Angiomotins have also been reported in the nucleus (80), and it will be interesting in future studies to determine whether they can regulate YAP/TAZ in the nucleus in response to changes in nuclear F-actin.…”
Section: Nuclear Actin Sensingmentioning
confidence: 99%
“…Intriguingly, the Hippo signaling pathway is regulated by a series of PPxY/WW-domain modular interactions which lead ultimately to either sequestration or degradation of phosphorylated YAP in the cytoplasm (Hippo on), or to localization of unphosphorylated YAP in the nucleus where it upregulates a series of TEAD genes involved in cell growth and proliferation (Hippo off) [58]. One of the key regulators of YAP/TAZ localization and Hippo pathway activity is angiomotin (Amot), a member of the angiomotin family (Amot, AmotL1, and AmotL2), all of which contain multiple PPxY motifs at their N-termini [59][60][61][62][63][64][65]. Indeed, the PPxY/WW-domain interaction between Amot and YAP is well-characterized and reported to affect multiple processes in the cell [60][61][62][64][65][66][67][68][69].…”
Section: -271) and Imcb (M-r02010mentioning
confidence: 99%
“…Angiomotins bind to both LATS1/2 and YAP and can inhibit YAP through two mechanisms: binding and retention of YAP in the cytoplasm/plasma membrane and activation of LATS1/2 (21, 24 -27). Other studies have shown that AMOT can control YAP nuclear/cytoplasmic localization, depending on its phosphorylation state (28). Angiomotins also bind the LATS1/2 activator NF2 (29,30), and a study using proximity labeling found that SAV1 and MOB1 may interact with AMOT (31).…”
mentioning
confidence: 98%